Oxygen environment and islet size are the primary limiting factors of isolated pancreatic islet survival - Komatsu, Hirotake; Cook, Colin; Wang, Chia-Hao; Medrano, Leonard; Lin, Henry; Kandeel, Fouad; Tai, Yu-Chong; Mullen, Yoko (PloS one, 2017)
Type 1 diabetes is an autoimmune disease that destroys insulin-producing beta cells in the pancreas. Pancreatic islet transplantation could be an effective treatment option for type 1 diabetes once several issues are resolved, including donor shortage, prevention of islet necrosis and loss in pre- and post-transplantation, and optimization of immunosuppression. This study seeks to determine the cause of necrotic loss of isolated islets to improve transplant efficiency. The oxygen tension inside isolated human islets of different sizes was simulated under varying oxygen environments using a computational in silico model. In vitro human islet viability was also assessed after culturing in different oxygen conditions. Correlation between simulation data and experimentally measured islet viability was examined. Using these in vitro viability data of human islets, the effect of islet diameter and oxygen tension of the culture environment on islet viability was also analyzed using a logistic regression model. Computational simulation clearly revealed the oxygen gradient inside the islet structure. We found that oxygen tension in the islet core was greatly lower (hypoxic) than that on the islet surface due to the oxygen consumption by the cells. The hypoxic core was expanded in the larger islets or in lower oxygen cultures. These findings were consistent with results from in vitro islet viability assays that measured central necrosis in the islet core, indicating that hypoxia is one of the major causes of central necrosis. The logistic regression analysis revealed a negative effect of large islet and low oxygen culture on islet survival. Hypoxic core conditions, induced by the oxygen gradient inside islets, contribute to the development of central necrosis of human isolated islets. Supplying sufficient oxygen during culture could be an effective and reasonable method to maintain isolated islets viable.